2017
DOI: 10.1039/c6tb02743a
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the protein corona around gold nanorods for low-dose combined photothermal and photodynamic therapy

Abstract: We load Ce6 onto NRs using its protein corona, deliver them to cells before performing laser irradiation for simultaneous PTT and PDT with greatly enhanced therapeutic efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 102 publications
(148 reference statements)
4
84
1
Order By: Relevance
“…59 Few other studies have incorporated the same strategy for multimodal cancer therapy and combined photodynamic therapy (PDT) and photothermal therapy (PTT). 60,61 Apart from this, prodrug nanoassemblies with exposed surface maleimide groups could effectively recruit albumin corona upon incubation in rat plasma. The presence of albumin enhanced their accumulation in tumor cells and also was showed better activity as compared to commercially available Abraxane®.…”
Section: Employing Protein Corona For Drug Loadingmentioning
confidence: 99%
“…59 Few other studies have incorporated the same strategy for multimodal cancer therapy and combined photodynamic therapy (PDT) and photothermal therapy (PTT). 60,61 Apart from this, prodrug nanoassemblies with exposed surface maleimide groups could effectively recruit albumin corona upon incubation in rat plasma. The presence of albumin enhanced their accumulation in tumor cells and also was showed better activity as compared to commercially available Abraxane®.…”
Section: Employing Protein Corona For Drug Loadingmentioning
confidence: 99%
“…However, the formation of this corona can also be employed as a targeting moiety or as drug transporter itself. Kah et al described the use of GNRs coated with a protein corona of human serum in which a photosensitizer (Chlorin e6) was loaded . The excitation at 665 nm generated fivefold‐times‐higher reactive oxidant species compared with free sensitizer, resulting in practically complete tumoral cell destruction at low dosages in the nanomolar range.…”
Section: Nanomaterials As Thermoseedsmentioning
confidence: 99%
“…Therefore, PC could be exploited as a biocompatible drug depot beside the therapeutic applications of NP itself. 31 In a preliminary study in this field in 2012, Kah et al 29 confirmed the possibility of DNA oligonucleotides and Doxorubicin loading onto PC around gold nanorods. By the same rationale, Shahabi et al 16 succeeded in an attempt to prepare a co-delivery system by loading hydrophilic doxorubicin and hydrophobic meloxicam onto fetal calf serum protein corona.…”
Section: Drug Loading On Corona-coated Gnpsmentioning
confidence: 98%
“…Therefore, the findings and previous reports inspired us to exploit protein corona as a sponge-like drug depot for the drugs in this study. In this regard, the PC around gold nanorods was used for loading a hydrophobic photosensitizer chlorin e6 solely for photodynamic/thermal therapy 31 and in combination with Doxorubicin for additional simultaneous chemotherapy. 32 In the previous studies, the colloidal stability of the nanoparticles was in a good condition after coating by PC.…”
Section: Drug Loading On Corona-coated Gnpsmentioning
confidence: 99%